The Palgrave handbook of state-sponsored history after 1945 - Bevernage, Berber; Wouters, Nico. (London : Palgrave Macmillan, 2018)
This handbook provides the first systematic integrated analysis of the role that states or state actors play in the construction of history and public memory after 1945. The book focuses on many different forms of state-sponsored history, including memory laws, monuments and memorials, state-archives, science policies, history in schools, truth commissions, historical expert commissions, the use of history in courts and tribunals et cetera The handbook contributes to the study of history and public memory by combining elements of state-focused research in separate fields of study. By looking at the state's memorialising capacities the book introduces an analytical perspective that is not often found in classical studies of the state. The handbook has a broad geographical focus and analyses cases from different regions around the world. The volume mainly tackles democratic contexts, although dictatorial regimes are not excluded.
State-Sponsored History after 1945: An Introduction / Berber Bevernage and Nico Wouters -- Part 1: Memory Laws and Legislated History -- Overview Chapter. Laws Governing the Historian's Free Expression / Antoon De Baets -- Case Studies -- Writing History through Criminal law: State-Sponsored Memory in Rwanda / Pietro Sullo -- French memory laws and the ambivalence about the meaning of colonialism / Stiina Löytömäki -- History Watch by the European Court of Human Rights / Pierre-Olivier de Broux and Dorothea Staes -- Legislated History in Post-Communist Lithuania / Tomas Balkelis and Violeta Davoliūtė -- Part 2: Archives and Libraries. Overview Chapter. Archives, Agency and the State / Trudy Huskamp Peterson -- Case Studies -- Open Archives to Close the Past: Bulgarian archival disclosure on the road to European Union accession / Niké Wentholt -- Archives and Post-Colonial State-Sponsored History: A dual state approach using the case of the "Migrated Archives" / Michael Karabinos -- The "Cleansing" of Croatian Libraries in the 1990s and Beyond or How (Not) to Discard the Yugoslav Past / Dora Komnenović -- Part 3: Research Institutes and Policies. Overview Chapter -- State Authority and Historical Research. Institutional Settings and Trends since 1945 / Lutz Raphael -- Case Studies -- Official History Reconsidered: The Tadhana Project in the Philippines / Rommel A. Curaming -- History riding on the waves of government coalitions. The first fifteen years of the Institute of National Remembrance in Poland (2001-2016) / Idesbald Goddeeris -- Part 4: Schools, Curricula and Textbooks -- Overview Chapter -- History in Schools / Peter Seixas -- Case Studies -- History teaching for the unification of Europe: The case of the Council of Europe / Luigi Cajani -- Teaching History under Dictatorship: The Politics of Textbooks and the Legitimation of Authority in Mobutu's Zaire / Denise Bentrovato -- The "National Dream" to Cultural Mosaic: State-Sponsored History in Canadian Education / Lynn Lemisko & Kurt W. Clausen -- China's history school curricula and textbook reform in East Asian context / Gotelind Müller -- Teaching History in Israel-Palestine / Achim Rohde -- Part 5: Museums and Musealisation. Overview Chapter -- History Museums / Ilaria Porciani -- Case Studies -- "State-supported history" at the local level: Ostdeutsche Heimatstuben and expellee museums in West Germany / Cornelia Eisler -- State Agency and the Definition of Historical Events: the case of the Museo de la Memoria y los Derechos Humanos in Santiago, Chile / Patrizia Violi -- History Wars in Germany and Australia: National Museums and the Re-legitimisation of nationhood / Christian Wicke and Ben Wellings -- Part 6: Memorials, Monuments and Heritage. Overview Chapter -- Memorials and state-sponsored history / Shanti Sumartojo -- Case Studies -- Spaces of nationhood and contested Soviet war monuments in Poland: the Warsaw Monument to the Brotherhood in Arms / Ewa Ochman -- Heritage Statecraft: transcending methodological nationalism in the Russian Federation / Gertjan Plets -- Part 7: Courts, Tribunals and Judicial History. Overview Chapter -- The State, the Courts, and the Lessons of History: An Overview, with Reference to Some Emblematic Cases / Richard J. Golsan -- Case Studies -- The Historian's Trial: John Demjanjuk and the Prosecution of Atrocity / Lawrence Douglas -- Germany vs. Germany: Resistance against Hitler, Postwar Judiciary and the 1952 Remer Case / Vladimir Petrovic -- Historical Testimony for the Government in US v. Philip Morris, et al. / Ramses Delafontaine -- A one-sided coin: A critical analysis of the legal accounts of the Cypriot conflicts / Nasia Hadjigeorgiou -- Part 8: Truth Commissions and Commissioned History. Overview Chapter -- Truth Commissions and the Construction of History / Eric Wiebelhaus-Brahm -- Case Studies -- Truth Commissions and the Politics of History: A Critical Appraisal / Stephan Scheuzger -- The Brazilian National Truth Commission (2012-2014) as a state-commissioned history project / Nina Schneider and Gisele Iecker de Almeida -- The 9/11 Commission Report: History Under the Sign of Memory / Oz Frankel -- Truths of the Dictatorship: Chile's Rettig and Valech Commissions as State-Sponsored History / Onur Bakiner -- Part 9: Historical Expert Commissions and Commissioned History. Overview Chapter -- Historical Expert Commissions and their Politics / Eva-Clarita Pettai -- Case Studies -- Reconstituting the Dutch State in the NIOD Srebrenica Report / Erna Rijsdijk -- Memory institutions and policies in Colombia: The historical memory group and the historical commission on the conflict and its victims / Martha Cecilia Herrera, José Gabriel Cristancho and Carol Juliette Pertuz -- Diversified and Globalized Memories: The Limits of State-Sponsored History Commissions in East Asia / Seiko Mimaki -- Switzerland's Independent Commission of Experts: State-Sponsored History and the Challenges of Political Partisanship / Alexander Karn -- Part 10: Official Apologies and Diplomatic History -- Overview Chapter -- Historical state apologies / Azuolas Bagdonas -- Case Studies -- Apology Failures: Japan's Strategies towards China and Korea in Dealing with its Imperialist Past / Torsten Weber -- The "Apology to Australia's Indigenous Peoples" in its Historical Context / Francesca Dominello -- Narrative Robustness, Post-Apology Conduct, and Canada's 1998 and 2008 Residential Schools Apologies / Matt James.
Keywords: History, Modern; World history; Military history; Social history; Civilization -- History